Business Model : “Grain for phone” initiative in AICCRA Communities - Kyeremeh, Emmanuel Marfo; Koi, Gordon Nii (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Esoko's "Grain for Phone" initiative aims to empower women and youth in agriculture by providing them with access to feature mobile phones through the exchange of harvested grain. This initiative will facilitate improved access to Climate Information Services (CIS) and Climate-Smart Agriculture (CSA) practices, directly benefiting participants and aligning with the objectives of the AICCRA project.